3(3p+1)=2(5p+6)

Simple and best practice solution for 3(3p+1)=2(5p+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3p+1)=2(5p+6) equation:


3(3p+1)=2(5p+6)

We simplify the equation to the form, which is simple to understand
3(3p+1)=2(5p+6)

Reorder the terms in parentheses
+(+9p+3)=2*(5p+6)

Remove unnecessary parentheses
+9p+3=+2+*(+5p+6+)

Reorder the terms in parentheses
+9p+3=+(+10p+12)

Remove unnecessary parentheses
+9p+3=+10p+12

We move all terms containing p to the left and all other terms to the right.
+9p-10p=+12-3

We simplify left and right side of the equation.
-1p=+9

We divide both sides of the equation by -1 to get p.
p=-9

See similar equations:

| 4k^2+48k=-128 | | 3x+8=6x-10 | | 8y-3=57+12 | | 5n+34=-2(17n) | | 4(2x-3)=6x-20 | | -6x-2+7x=8 | | -19=-3x-4x+9 | | 7x^2-800x+10000=0 | | (x+1)(5x-5)=-98 | | (x-5)(5x+1)=-5 | | 8a+5b+2b-5a= | | 66-7x=11x+18 | | x*2-5=3 | | 37-4*7= | | 8a+5b=2b-5a | | 2x+92=9x-13 | | x^4-4x^3=40+17x | | -4+x-3x-7=-33 | | x^4-4x^3-17x=40 | | p^4-16q^4= | | 3x+2+5x=45 | | -3y=-7-x | | x-3y+7=0 | | 2+2X^3=0 | | 2x+1+x=-14 | | -10+x+7x=62 | | x^2+4x-41=4 | | z+3(z-4)=5 | | 70=4x+2x+10 | | 2+4x-2x=14 | | 6-3x-6x=42 | | 32a-8=-30a |

Equations solver categories